THE EFFECT OF CREATIVITY LEARNING MODEL ON LEARNING INTEREST AND LEARNING OUTCOMES OF NATURAL SCIENCE IN GRADE 5 STUDENTS BASED ON CLASS I CLUSTER BULELENG DISTRICT - Ida Ayu Made Indah Padmitasari; I Gusti Ayu Tri Agustiana; Gede Wira Bayu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Learning process is a learning activity for students which can cause the changes of students’ behavior that also called as learning interest. Student learning interests affect student enthusiasm and activeness in the learning process. So students have high spirits to be able to improve learning outcomes. One of the learning models that can be used to increase students’ learning interest and learning outcomes in natural science subjects is the creativity learning model.This study aims to determine the effect of the creativity learning model on learning interest and learning outcomes of natural sciences in grade 5 students of Elementary School I Cluster Buleleng District. This research was a quasi-experimental study with a nonequivalent posttest only control group research design. The populations in this study were all fifth grade students of Elementary School I Cluster Buleleng District totaling 209 students. The sample of this research was the fifth grade students of SDN 1 Banyuning as an experimental group totaling 29 students and the fifth grade students of SDN 8 Banyuning as a control group totaling 30 students. This study used test and non-test methods, learning interest data were collected using a questionnaire and data on natural science learning outcomes were collected using essay tests. Data were analyzed with descriptive statistics and the MANOVA test. The average scores of the questionnaire for learning interest in the experimental group was 116.14 with